Delineation of CCDC39/CCDC40 mutation spectrum and associated phenotypes in primary ciliary dyskinesia. Issue 6 (12th June 2012) - Blanchon, Sylvain; Legendre, Marie; Copin, Bruno; Duquesnoy, Philippe; Montantin, Guy; Kott, Esther; Dastot, Florence; Jeanson, Ludovic; Cachanado, Marine; Rousseau, Alexandra; Papon, Jean François; Beydon, Nicole; et al.
Abstract : Background: CCDC39 and CCDC40 genes have recently been implicated in primary ciliary dyskinesia (PCD) with inner dynein arm (IDA) defects and axonemal disorganisation; their contribution to the disease is, however, unknown. Aiming to delineate the CCDC39/CCDC40 mutation spectrum and associated phenotypes, this study screened a large cohort of patients with IDA defects, in whom clinical and ciliary phenotypes were accurately described. Methods: All CCDC39 and CCDC40 exons and intronic boundaries were sequenced in 43 patients from 40 unrelated families. The study recorded and compared clinical features (sex, origin, consanguinity, laterality defects, ages at first symptoms and at phenotype evaluation, neonatal respiratory distress, airway infections, nasal polyposis, otitis media, bronchiectasis, infertility), ciliary beat frequency, and quantitative ultrastructural analyses of cilia and sperm flagella. Results: Biallelic CCDC39 or CCDC40 mutations were identified in 30/34 (88.2%) unrelated families with IDA defects associated with axonemal disorganisation (22 and eight families, respectively). Fourteen of the 28 identified mutations are novel. No mutation was found in the six families with isolated IDA defects. Patients with identified mutations shared a similar phenotype, in terms of both clinical features and ciliary structure and function. The sperm flagellar ultrastructure, analysed in 4/7 infertile males, showed evidence of abnormalities similar to the ciliary ones. Conclusions: CCDC39 and CCDC40 mutations represent the major cause of PCD with IDA defects and axonemal disorganisation. Patients carrying CCDC39 or CCDC40 mutations are phenotypically indistinguishable. CCDC39 and CCDC40 analyses in selected patients ensure mutations are found with high probability, even if clinical or ciliary phenotypes cannot prioritise one analysis over the other.